Factors Affecting Employee Motivation in Selected Local Government Units (LGUs) in Davao Del Norte - Tan, Jhaca Jones N.; Cemini, Jinedeth T.; Morente, Glenn Froyd N.; Castro III, Modesto Carlos S.; Saromines, Gemar S.; Pormento, Shemar Jove H. (Future Science / FSH-PH Publications, 2025)
This quantitative descriptive-correlational research aimed to investigate the factors affecting employee motivation in selected local government units (LGUs) in Davao del Norte. In this study, 365 employees from various LGUs participated, providing insights into how financial incentives, career development, promotional opportunities, and job security influence their motivation levels. The researchers used adopted research instruments to assess the variables. Data were analyzed using statistical tools like Mean, Standard Deviation, Pearson Correlation Coefficient (r), and Regression Analysis. Based on the results of the study, financial incentives, career development, promotional opportunities, and job security collectively scored very high, indicating that these factors are evident at a very large extent. Similarly, the level of employee motivation among employees is evident to a very great extent. The findings further show that there is a significant relationship between factors affecting motivation and employee motivation among employees. The results also showed that the factors affecting motivation significantly predict the employee motivation among LGU employees in Davao Del Norte. The findings suggest that enhancing these influencing factors can effectively lead to increased levels of employee motivation. Based on these findings, the study recommends maintaining and increasing financial rewards, investing in career development and job security programs. Also, the Human Resource Department of each LGU may implement transparent, merit-based promotion policies aligned with organizational goals and employee performance. They may also foster employee well-being by introducing programs such as team-building activities, wellness initiatives, and recognition awards to build a motivating and supportive workplace.